Airway Administration of Bacterial Lysate OM-85 Protects Mice Against Respiratory Syncytial Virus Infection - Antunes, Krist Helen; Cassão, Gisele; Santos, Leonardo Duarte; Borges, Sofia Giacomet; Poppe, Juliana; Gonçalves, João Budelon; Nunes, Eduarda da Silva; Recacho, Guilherme Fernando; Sousa, Vitória Barbosa; Da Silva, Gabriela Souza; Mansur, Daniel; Stein, Renato T.; et al. (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) is a seasonal pathogen responsible for the highest percentage of viral bronchiolitis in pediatric patients, causing approximately 190,000 deaths per year worldwide among children under 5 years old, generating a great impact on public health. There are currently no vaccine available and therapeutic methods to mitigate the severity of RSV bronchiolitis are limited. OM-85, an oral standardized bacterial lysate isolated from human respiratory pathogenic strains and widely used to prevent recurrent infections and/or exacerbations in populations at risk, has been shown to be effective and safe in children and adults. It has demonstrated protection against allergic inflammation as well as bacterial and viral respiratory infections such as SARS-CoV-2, H1N1 and rhinovirus infection. OM-85 activates different immune mechanisms by modulating dendritic cells, T cells, and induces type I interferon with improved immune response, through the release of various anti-inflammatory mediators. Here, we demonstrate that airway administration of OM-85 in mice prevents RSV-induced disease, resulting in lower viral replication, and less perivascular and peribronchial inflammation in the lungs. In addition, OM-85 has showed to increase alveolar macrophages, Treg and Th1expansion in the lung, even in the absence of infection, contributing to a better Th1/Th2 balance and preventing ILC2 recruitment in the airways. OM-85 preventive treatment also improved antiviral response by increasing IFNβ and its responsive genes in the lung. In vitro, OM-85 protects against RSV infection in a type I interferon pathway. Our animal model data suggest that intranasal use of OM-85 should be considered as a potential prophylactic product to prevent RSV bronchiolitis once human studies confirm these findings.